Clinical prediction in early pregnancy of infants small for gestational age by customised birthweight centiles: findings from a healthy nulliparous cohort. - Lesley M E McCowan; John M D Thompson; Rennae S Taylor; Robyn A North; Lucilla Poston; Philip N Baker; Jenny Myers; Claire T Roberts; Gustaaf A Dekker; Nigel A B Simpson; James J Walker; Louise C Kenny; et al. (PLoS ONE)
Objective Small for gestational age (SGA) infants comprise up to 50% of all stillbirths and a minority are detected before birth. We aimed to develop and validate early pregnancy predictive models for SGA infants. Methods 5628 participants from SCOPE, a prospective study of nulliparous pregnant women, were interviewed at 15 ± 1 weeks' gestation. Fetal anthropometry, uterine and umbilical Doppler studies were performed at 20 ± 1 weeks'. The cohort was divided into training (n = 3735) and validation datasets (n = 1871). All-SGA (birthweight <10th customised centile), Normotensive-SGA (SGA with normotensive mother) and Hypertensive-SGA (SGA with mother who developed hypertension) were the primary outcomes. Multivariable analysis was performed using stepwise logistic regression firstly using clinical variables and then with clinical and ultrasound variables. Receiver operator curves were constructed and areas under the curve (AUC) calculated. Results 633 infants (11.3%) in the whole cohort were SGA; 465 (8.3%) Normotensive-SGA and 165 (3.0%) Hypertensive-SGA. In the training dataset risk factors for All-SGA at 15 ± 1 weeks' included: family history of coronary heart disease, maternal birthweight <3000 g and 3000 g to 3499 g compared with ≥ 3500 g, >12 months to conceive, university student, cigarette smoking, proteinuria, daily vigorous exercise and diastolic blood pressure ≥ 80. Recreational walking ≥ 4 times weekly, rhesus negative blood group and increasing random glucose were protective. AUC for clinical risk factors was 0.63. Fetal abdominal or head circumference z scores <10(th) centile and increasing uterine artery Doppler resistance at 20 ± 1 weeks' were associated with increased risk. Addition of these parameters increased the AUC to 0.69. Clinical predictors of Normotensive and Hypertensive-SGA were sub-groups of All-SGA predictors and were quite different. The combined clinical and ultrasound AUC for Normotensive and Hypertensive-SGA were 0.69 and 0.82 respectively. Conclusion Predictors for SGA of relevance to clinical practice were identified. The identity and predictive potential differed in normotensive women and those who developed hypertension.